Expression profile analysis of microRNAs in prostate cancer by next‐generation sequencing. Issue 5 (16th January 2015) - Song, Chunjiao; Chen, Huan; Wang, Tingzhang; Zhang, Weiguang; Ru, Guomei; Lang, Juan
<x xml:space="preserve">Abstract</x> BACKGROUND Prostate cancer (PCa) is the second leading cause of tumor mortality among males in western societies. In China, the diagnostic and fatality rate of PCa is increasing yearly. METHODS To characterize underlying molecular mechanisms, the microRNA (miRNA) profile of high‐grade PCa, low‐grade PCa, and benign prostate hyperplasia (BPH) were compared using high‐throughput Illumina sequencing and quantitative real‐time PCR (qRT‐PCR) methods. Moreover, a variety of biological information softwares and databases were applied to predict the target genes of miRNA, molecular functions, and signal pathways. RESULTS Eighteen miRNAs were differentially expressed (fold change ≥2, P < 0.05), of which thirteen were upregulated and five were downregulated by sequencing. This was confirmed by qRT‐PCR in more clinical tissue samples. In the tumors, miRNAs (miR‐125b‐5p, miR‐126‐5p, miR‐151a‐5p, miR‐221‐3p, and miR‐222‐3p) were significantly upregulated with downregulation of miR‐486‐5p. In addition, 13 novel miRNAs were identified from three prostate tissue libraries, with 12 of them assayed in 21 human normal tissues by qRT‐PCR. Multiple databases indicated target genes for these differentially expressed miRNAs. Function annotation of target genes indicated that most of them tend to target genes involved in signal transduction and cell communication, especially cancer‐related PI3K‐Akt and p53 signaling pathway. CONCLUSIONS The small RNA transcriptomes obtained in this study uncovers six differentially expressed miRNAs and 12 novel miRNAs, and provides a better understanding of the expression and function of miRNAs in the development of PCa and reveals several miRNAs in PCa that may have biomarker and therapeutic potentials. Prostate 75: 500–516, 2015. © 2015 Wiley Periodicals, Inc.